A simple sequence repeats marker of disease resistance in shrimp Litopenaeus vannamei and its application in selective breeding - Yin, Bin; Wang, Haiyang; Weng, Shaoping; Li, Sedong; He, Jianguo; Li, Chaozheng (Frontiers in Genetics, 2023)
The polymorphism of the simple sequence repeat (SSR) in the 5′ untranslated coding region (5′-UTR) of the antiviral gene IRF (LvIRF) has been shown to be implicated in the resistance to viral pathogens in shrimp Litopenaeus vannamei (L. vannamei). In this study, we explored the potential of this (CT)n-SSR marker in disease resistance breeding and the hereditary property of disease resistance traits in offspring. From 2018 to 2021, eight populations were generated through crossbreeding by selecting individuals according to microsatellite genotyping. Our results demonstrated that shrimp with the shorter (CT)n repeat exhibited higher resistance to white spot syndrome virus (WSSV) or Decapod iridescent virus 1 (DIV1); meanwhile, these resistance traits could be inherited in offspring. Interestingly, we observed that the longer (CT)n repeats were associated with bacterial resistance traits. Accordingly, shrimp with longer (CT)n repeats exhibited higher tolerance to Vibrio parahaemolyticus infection. Taken together, these results indicate that the single (CT)n-SSR marker could be used to selective breeding for both resistance to virus and bacteria in shrimps.